Diversity of bat ectoparasites from the caves of selected Key Biodiversity Areas in Central Visayas, Philippines - GILBERT A. BEJEC; LILIBETH A. BUCOL; AGUSTIN B. ANCOG; ALBERT C. PAGENTE; JAZZE JANE M. PANERIO; ANNA LEE N. BEJEC; JACINTO D. BELANIZO; DENNY JANE S. TUASTOMBAN; REIZL P. JOSE (Society for Indonesian Biodiversity, 2023)
Abstract. Bejec GA, Bucol LA, Ancog AB, Pagente AC, Paneiro JJM, Bejec ALN, Belanizo JD, Tuastomban DJS, Jose RP. 2023. Diversity of bat ectoparasites from the caves of selected Key Biodiversity Areas in Central Visayas, Philippines. Biodiversitas 24(3): 1693-1703. Bats harbor numerous species of ectoparasites, such as ticks and mites. Many bat ectoparasites are implicated as vectors of pathogens ranging from bacteria to protozoa and viruses. Recent studies verified bats as a natural reservoir of multiple zoonotic viruses, including Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS) coronaviruses. This study assessed the composition, diversity, and prevalence of ectoparasites of cave-dwelling bats in the four Key Biodiversity Areas (KBAs) of Central Visayas. A total of 20 species of bats were recorded in the 30 surveyed caves. Of these, 30 species of ectoparasites belonging to eight families (dipteran flies Streblidae and Nycteribiidae, mites Spinturnicidae, Macronyssidae and Trombiculidae, ticks Argasidae and Ixodidae, and Ischnopsyllidae fleas) were collected and identified. Leptotrombidium sp. had the highest number of individuals (n=1,684) harbored in 12 bat host species. The highest prevalence (100%) was noted in four bat host species: Philippine pygmy fruit bat Haplonycteris fischeri Lawrence 1939, Philippine forest roundleaf bat Hipposideros obscurus Peters 1861, Philippine pygmy roundleaf batHipposideros pygmaeus Waterhouse 1843, and Common bent-winged bat Miniopterus schreibersii Kuhl 1817. The lowest prevalence was noted in the Round-eared tube-nosed bat Murina cyclotis Dobson 1872, where no ectoparasite was collected. The highest intensity (n=65) of ectoparasites was observed in the Common Asian ghost bat Megaderma spasma Linnaeus 1758. This study provides essential data for future reference in monitoring bat population status and conservation efforts in the region. Given the close relationship between the local human community and bats (e.g., hunting and consumption), more work is needed to address the potential pathogen risks from zoonotic transmission from bats and ectoparasites.